2008
DOI: 10.1002/ar.20764
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐Derived Growth Factor Receptor‐Alpha‐Expressing Cells Localize to the Alveolar Entry Ring and Have Characteristics of Myofibroblasts During Pulmonary Alveolar Septal Formation

Abstract: Platelet‐derived growth factor‐A and its receptor, platelet‐derived growth factor receptor‐alpha (PDGF‐Rα), are required for formation of the secondary pulmonary alveolar septa in mice. However, it remains unclear how these molecules direct the secondary septation process. We have examined the abundance, location, and the accumulation of alpha‐smooth muscle actin (αSMA), neutral lipid droplets, and elastin in the proximity of PDGF‐Rα‐expressing alveolar cells during postnatal days 4 through 12 in the mouse. PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
133
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(149 citation statements)
references
References 27 publications
14
133
1
Order By: Relevance
“…The pdgf-r␣ expressing LF population increases between P4 and P8 through proliferation (13) and maintains its abundance until at least P12 (19). We have now shown that the pdgfr␣-expressing population diminishes after P12 because of apoptosis and diminished proliferation, resulting in fewer and thinner alveolar walls.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The pdgf-r␣ expressing LF population increases between P4 and P8 through proliferation (13) and maintains its abundance until at least P12 (19). We have now shown that the pdgfr␣-expressing population diminishes after P12 because of apoptosis and diminished proliferation, resulting in fewer and thinner alveolar walls.…”
Section: Discussionmentioning
confidence: 62%
“…Our previous studies showed that pdgf-r␣ expressing alveolar cells increased from P4 to P12 (19). To determine whether this increase was influenced by PDGF-R␣ function, we exposed mice to imatinib.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The type 1 cells line the entire alveolar epithelial surface and run adjacent to capillaries in the underlying mesenchyme, providing a minimal barrier for gas exchange. The mesenchyme of the alveoli also contains alveolar smooth muscle cells and stromal fibroblasts, including lipofibroblasts and myofibroblasts, although these cell types may be interconvertible (Kapanci et al, 1974;Lindahl et al, 1997;McGowan et al, 2008;Perl and Gale, 2009). In all regions of the lung, it is difficult to distinguish the different mesenchymal cells, either morphologically or with molecular markers, and there may be additional undescribed subtypes.…”
Section: Lung Structurementioning
confidence: 99%
“…Type 1 AECs (AEC1s), which are flat and occupy the large part of alveolar surface, are involved in gas exchange, whereas type 2 AECs (AEC2s), which are small and cuboidal cells, secrete surfactants to lower the surface tension of lungs (1,2). During secondary septation, alveolar myofibroblast (AMYF) precursors expressing platelet-derived growth factor-receptor-α subunit (PDGFRα) are induced by epithelial-derived PDGF-A and differentiate into AMYFs (3)(4)(5)(6). AMYFs expressing contractile α-smooth muscle actin (α-SMA) transiently appear at the tips of the new alveolar septa from postnatal day (P) 5 and deposit extracellular matrix (ECM) proteins, including tropoelastin, collagen, and fibronectin, which provide the driving force for folding up of interalveolar walls (7)(8)(9).…”
mentioning
confidence: 99%